Dicer Is Required for the Transition from Early to Late Progenitor State in the Developing Mouse Retina - Georgi, Sean A. (Society for Neuroscience, 2010)
MicroRNAs (miRNAs), small 19–25 nucleotide RNAs that influence gene expression through posttranscriptional regulation of mRNA translation and degradation, have recently emerged as important regulators of neural development. Using conditional knock-out of Dicer, an RNase III enzyme required for miRNA maturation, previous studies have demonstrated an essential role for miRNAs in mouse cortical, inner ear, and olfactory development. However, a previous study (Damiani et al., 2008) using a Chx10cre mouse to delete Dicer in retinal progenitors reported no defects in the retina before the second postnatal week, suggesting that miRNAs are not required for mouse retinal development. In an effort to further study the role of miRNAs during retinal development and resolve this apparent conflict, we conditionally knocked out Dicer using a different (αPax6cre) line of transgenic mice. In contrast to the previous study, we demonstrate an essential role for miRNAs during mouse retinal development. In the absence of Dicer in the embryonic retina, production of early generated cell types (ganglion and horizontal cells) is increased, and markers of late progenitors are not expressed. This phenotype persists into postnatal retina, in which we find the Dicer-deficient progenitors fail to generate late-born cell types such as rods and Müller glia but continue to generate ganglion cells. We further characterize the dynamic expression of miRNAs during retinal progenitor differentiation and provide a comprehensive profile of miRNAs expressed during retinal development. We conclude that Dicer is necessary for the developmental change in competence of the retinal progenitor cells.